Intelligent piezoelectric response polymer-based self-lubricating material as well as preparation method and application thereof

By using intelligent piezoelectric responsive polymer-based self-lubricating materials in robot joints, using the combination of piezoelectric powder and polymer, intelligent self-lubricating and high wear resistance under dry friction conditions are achieved, solving traditional materials The high wear and power waste problems extend the service life of the robot joints.

CN119286170AActive Publication Date: 2025-01-10QINGDAO UNIV OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411637889.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Traditional robot joint self-lubricating materials have large friction coefficient and high wear rate under dry friction conditions, resulting in waste of power and fast loss of joint materials, and it is difficult to achieve intelligent self-lubricating function.

Method used

Using intelligent piezoelectric responsive polymer-based self-lubricating material, which consists of piezoelectric powder and piezoelectric polymer, prepared by melt blending and molding, it can convert mechanical energy into electrical energy under pressure response and form homogeneous charges. Repulsion effect, reducing friction and wear.

Benefits of technology

It significantly improves the lubricity and wear resistance of robot joints, reduces friction coefficient and wear rate, extends the service life of the joint, simplifies the preparation process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286170A_ABST
    Figure CN119286170A_ABST
Patent Text Reader

Abstract

The invention discloses an intelligent piezoelectric response polymer-based self-lubricating material as well as a preparation method and application thereof, and belongs to the field of robots. The material comprises the following components in percentage by volume: 1-15% of piezoelectric powder and 85-99% of piezoelectric high-molecular polymer, the piezoelectric powder is an oxide containing bismuth and other metals, or a compound of the oxide and a carbon material. The intelligent piezoelectric response polymer-based self-lubricating material provided by the invention has good self-lubricating property, wear resistance and piezoelectric property, on the premise of realizing joint movement of a robot, mechanical energy is converted into electric energy under pressure response, homogeneous charges are formed on an interface, and mutual repulsive charges can prevent interaction of the interface, so that friction is reduced, and the robot joint movement is realized. And the abrasion is reduced, the intelligent self-lubricating effect is formed, extra power loss is saved, and the technical problem that lubrication is frequently replaced due to the fact that a traditional robot active joint is abraded seriously or uses oil, lean oil, grease and other liquid lubricants under the dry friction condition is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of robots and relates to the technical field of robot movable joint materials, and specifically to an intelligent piezoelectric responsive polymer-based self-lubricating material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Joints are an important part of the human skeletal system. They need to have mobility, stability, shock absorption and wear resistance, coordination and flexibility in the human body. Since joints can ensure the movement between connected bones, the body can perform various complex movements and postures. Some joints need to have the ability to absorb shock and pressure to protect the body from injury. Through the mutual cooperation between joints, bones and muscles, the body's movements are more coordinated and smooth, allowing the body to move in different directions. In the field of robotics, joints are also crucial. Because the robot's operating environment is very complex, such as underwater, desert and other environments, it is difficult to use oil, less oil or grease lubrication on the joints. Therefore, the intelligent conversion of mechanical force at the interface of the joints under dry friction conditions, intelligent self-lubrication, shock absorption and wear resistance are more important. If no protective measures are taken, the robot will have low operating efficiency and shortened life.

[0004] The joints of the robot require self-lubricating materials. Traditional self-lubricating materials cannot achieve intelligent transformation of interface mechanical forces, have large friction damping, and a small operating temperature range, which affects the service life and application scope of high-speed parallel robots.

[0005] Chinese patent CN116925483A discloses a lightweight wear-resistant polytetrafluoroethylene self-lubricating composite material, which blends polyethersulfone with polytetrafluoroethylene to prepare a polyethersulfone / polytetrafluoroethylene composite material with excellent friction reduction and wear resistance, good thermal stability, light weight and low cost, and applies it to the field of drones and robots in engineering practice teaching, which will effectively improve the performance and life of its moving parts. Its advantages are that it has self-lubricating, self-repairing and self-protection functions, which effectively improves the performance and life of robot moving parts; its disadvantages are: complex preparation, poor self-lubricating effect, inability to realize intelligent conversion of interface mechanical force, no intelligent self-lubricating function, still need to use lubricating oil, and need to further improve the self-lubricating effect to realize intelligent self-lubricating of robot joints under dry friction conditions. Summary of the invention

[0006] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide an intelligent piezoelectric responsive polymer-based self-lubricating material and a preparation method and application thereof. The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention can convert mechanical energy into electrical energy under pressure response conditions, and homogeneous charges are formed on the interface. The mutually repelling charges can reduce friction, reduce wear, and form an intelligent self-lubricating effect, thereby solving the problems in the prior art of power waste caused by the large friction coefficient of the robot joint under dry friction conditions and rapid loss of joint materials caused by the large wear rate.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] The first aspect of the present invention provides an intelligent piezoelectric responsive polymer-based self-lubricating material, which comprises, by volume percentage: 1-15% piezoelectric powder, 85-99% piezoelectric high molecular polymer;

[0009] The piezoelectric powder is an oxide containing bismuth and other metals, or a composite of the oxide and a carbon material.

[0010] In some embodiments of the present invention, the piezoelectric powder is selected from at least one of bismuth ferrite, bismuth tungstate, bismuth vanadate, bismuth niobate, bismuth ferrite / graphene oxide composite, bismuth tungstate / graphene oxide composite, bismuth vanadate / graphene oxide composite, bismuth niobate / graphene oxide composite, bismuth ferrite / carbon nanotube composite, bismuth tungstate / carbon nanotube composite, bismuth vanadate / carbon nanotube composite and / or bismuth niobate / carbon nanotube composite.

[0011] In some embodiments of the present invention, the piezoelectric powder is micro-nano powder.

[0012] In some embodiments of the present invention, the piezoelectric polymer includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11, perfluoroethylene propylene copolymer, modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 and / or modified perfluoroethylene propylene copolymer.

[0013] In some embodiments of the present invention, the modification is to use a conductive alkyl imidazole ionic liquid as a modifier, and obtain modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 or modified perfluoroethylene propylene copolymer by melt blending.

[0014] In some embodiments of the present invention, the alkyl imidazole ionic liquid is one of 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate and 1-butyl-3-methylimidazolium hydrogen sulfate.

[0015] In some embodiments of the present invention, the volume percentage includes: 1-10% piezoelectric powder and 90-99% piezoelectric high molecular polymer.

[0016] In some embodiments of the present invention, the composition comprises, by volume percentage: 1-10% piezoelectric powder, 90-99% piezoelectric high molecular polymer;

[0017] The piezoelectric powder is one of bismuth ferrite, bismuth tungstate, bismuth vanadate or bismuth niobate.

[0018] In some embodiments of the present invention, the composition comprises, by volume percentage: 5% piezoelectric powder, 95% piezoelectric high molecular polymer;

[0019] The piezoelectric powder is bismuth ferrite, and the piezoelectric high molecular polymer is polyvinylidene fluoride.

[0020] In some embodiments of the present invention, the composition comprises, by volume percentage: 3-7% piezoelectric powder, 93-97% piezoelectric high molecular polymer;

[0021] The piezoelectric powder is one of bismuth ferrite, bismuth tungstate, bismuth vanadate or bismuth niobate;

[0022] The piezoelectric high molecular polymer is a material modified by melt blending with alkyl imidazole ionic liquid as a modifier and polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11 or perfluoroethylene-propylene copolymer as a polymer matrix.

[0023] In some embodiments of the present invention, the composition comprises, by volume percentage: 5% piezoelectric powder, 95% piezoelectric high molecular polymer;

[0024] The piezoelectric powder is bismuth ferrite, and the piezoelectric high molecular polymer is polyvinylidene fluoride modified by alkyl imidazole ionic liquid.

[0025] The second aspect of the present invention provides a method for preparing the above-mentioned intelligent piezoelectric responsive polymer-based self-lubricating material, comprising:

[0026] The piezoelectric powder and the piezoelectric high molecular polymer are mixed in proportion to obtain a mixed material, and the mixed material is molded to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

[0027] In some embodiments of the present invention, the forming is compression molding or injection molding;

[0028] The compression molding has a molding pressure of 6-24 MPa and a molding temperature of 350-390°C.

[0029] The third aspect of the present invention provides an application of the above-mentioned intelligent piezoelectric responsive polymer-based self-lubricating material or the intelligent piezoelectric responsive polymer-based self-lubricating material prepared by the above-mentioned preparation method in a robot.

[0030] In some embodiments of the present invention, smart piezoelectric responsive polymer-based self-lubricating materials are used in movable joints of robots.

[0031] The beneficial effects of the present invention are:

[0032] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention has good wear resistance, piezoelectric response, and intelligent self-lubricating properties. The material can convert mechanical energy into electrical energy under pressure response, accumulate homogeneous charges at the interface, form a repulsion effect, and thus improve lubricity and wear resistance. The present invention adds a specific proportion of piezoelectric powder to the piezoelectric macromolecular polymer, and the intelligent response interface converts pressure into electrical energy, forms homogeneous charge repulsion, and blocks the interaction of the material interface, thereby reducing the friction coefficient, increasing anti-wear performance, and reducing energy dissipation. The present invention changes the intelligent self-lubrication, wear resistance, and piezoelectric response characteristics of the obtained intelligent piezoelectric responsive polymer-based self-lubricating material by changing the type and ratio of the piezoelectric macromolecular polymer, and can prepare intelligent piezoelectric responsive polymer-based self-lubricating materials that meet different performance requirements according to actual needs.

[0033] The preparation method of the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention is simple, has low preparation cost, and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] Figure 1 The diagram is a synthesis reaction mechanism diagram of bismuth ferrite / carbon nanotube composite, which shows that the reaction example is applicable to all piezoelectric materials;

[0036] Figure 2 It is a diagram of polymer modification and its preparation mechanism;

[0037] Figure 3 A diagram of the charge repulsion mechanism of the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention;

[0038] Figure 4 The schematic diagram of the piezoelectric machine of the intelligent piezoelectric response polymer-based self-lubricating material provided by the present invention;

[0039] Figure 5 This is a SEM image of bismuth ferrite prepared in Example 1 of the present invention;

[0040] Figure 6 A graph showing the change in friction coefficient between the smart piezoelectric responsive polymer-based self-lubricating material provided in Example 1 of the present invention and pure PVDF material under different pressures;

[0041] Figure 7 A wear variation diagram of the intelligent piezoelectric responsive polymer-based self-lubricating material provided in Example 1 of the present invention and pure PVDF material under different pressures;

[0042] Figure 8 A graph showing a change in the friction coefficient of the intelligent piezoelectric responsive polymer-based self-lubricating material provided in Examples 5-7 of the present invention under a pressure of 10N;

[0043] Fig. 9 This is a graph showing the wear variation of the intelligent piezoelectric responsive polymer-based self-lubricating material provided in Examples 5-7 of the present invention under a pressure of 10N. DETAILED DESCRIPTION

[0044] It should be noted that the term intelligent self-lubrication refers to the lubrication phenomenon that converts mechanical energy into electrical energy. The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention has an intelligent self-lubricating function, which can convert mechanical energy into electrical energy under pressure response, and form homogeneous charges at the interface. The mutually repelling charges can prevent the interaction of the interface, thereby reducing friction and wear, forming an intelligent self-lubricating effect, saving additional power loss, and solving the lubrication technology problem of traditional robot active joints under dry friction conditions due to large wear or the use of liquid lubricants such as oil, lean oil, and grease, which requires frequent replacement.

[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] A first typical embodiment of the present invention provides an intelligent piezoelectric responsive polymer-based self-lubricating material, which comprises, by volume percentage: 1-15% piezoelectric powder, 85-99% piezoelectric high molecular polymer;

[0047] The piezoelectric powder is an oxide containing bismuth and other metals, or a composite of the oxide and a carbon material.

[0048] In the field of robotics, the robot's active working environment is very complex and alternating, such as underwater, desert, space and other environments. It is difficult to use oil, less oil or grease to lubricate the joints. Therefore, the self-lubrication (especially intelligent self-lubrication) and shock absorption and wear resistance of the joints under dry friction conditions are more important. In this regard, the present invention uses piezoelectric powder and piezoelectric macromolecular polymer to prepare an intelligent piezoelectric responsive polymer self-lubricating material with good piezoelectric properties. Compared with the prior art, the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention has good intelligent self-lubricating property, wear resistance and piezoelectric performance. Under the premise of realizing the joint movement of the robot, the material can convert mechanical energy into electrical energy under pressure response, and the interface forms homogeneous charges. The mutually repelling charges can prevent the interaction of the interface to reduce friction, reduce wear, form an intelligent self-lubricating effect, save additional power loss, and solve the problem of lubrication technology that the active joints of traditional robots are frequently replaced due to large wear or the use of liquid lubricants such as oil, lean oil, and grease under dry friction conditions.

[0049] Furthermore, other powders may be added to the smart piezoelectric responsive polymer-based self-lubricating material provided by the present invention to further modify the material, such as adding other powders to change the energy consumption problem.

[0050] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the content of piezoelectric powder can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15% by volume; the content of the piezoelectric high molecular polymer can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%.

[0051] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the piezoelectric powder is selected from at least one of bismuth ferrite (BiFeO3), bismuth tungstate (Bi2WO6), bismuth vanadate (BiVO4), bismuth niobate (Bi3NbO7), bismuth ferrite / graphene oxide composite (BiFeO3@GrO), bismuth tungstate / graphene oxide composite (Bi2WO6@GrO), bismuth vanadate / graphene oxide composite (BiVO4@GrO), bismuth niobate / graphene oxide composite (Bi3NbO7@GrO), bismuth ferrite / carbon nanotube composite (BiFeO3@CNTs), bismuth tungstate / carbon nanotube composite (Bi2WO6@CNTs), bismuth vanadate / carbon nanotube composite (BiVO4@CNTs) and / or bismuth niobate / carbon nanotube composite (Bi3NbO7@CNTs).

[0052] The piezoelectric powder has piezoelectricity, lubricity and wear resistance, excellent ferroelectricity and antiferromagnetism, high mechanical strength, chemical stability, corrosion resistance to acids, alkalis and organic solutions, and is easy to generate homogeneous charges during friction. Its excellent high wear resistance, piezoelectric response and lubricity can reduce the power loss caused by joint movement. The antiferromagnetic Nye point of the piezoelectric powder is 370-450°C, which means that it can exhibit multiferroicity and generate homogeneous charge characteristics at room temperature, indicating that these materials have great application potential in many fields.

[0053] The piezoelectric powder is added to the piezoelectric macromolecular polymer to improve the wear resistance and piezoelectric response of the piezoelectric macromolecular polymer, thereby improving the intelligent self-lubricating property of the intelligent piezoelectric responsive polymer-based self-lubricating material.

[0054] It should be noted that the bismuth ferrite, bismuth tungstate, bismuth vanadate and bismuth niobate in the above-mentioned piezoelectric powders are conventional products, which can be purchased commercially or prepared by oneself.

[0055] Bismuth ferrite, bismuth tungstate, bismuth vanadate and bismuth niobate can be prepared by the following method.

[0056] Preparation method of bismuth ferrite powder:

[0057] According to the required molar mass fraction, the molar ratio of Bi to Fe is 1:1, and bismuth ions Bi are provided to 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) 3+ ) and ferrous sulfate (Fe2(SO4)3·7H2O, 0.1 mol / L, providing iron ions Fe 3+ ) solution until the bismuth ions and iron ions in the mixed solution are completely precipitated, filtered with deionized water, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used for stirring to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out. After the reaction is completed, the bismuth ferrite powder is obtained by filtering and drying.

[0058] The reaction temperature of the hydrothermal reaction is 200°C and the reaction time is 24h. The temperature and time will affect the purity of bismuth ferrite. At the above temperature and time, the purity of all bismuth ferrites is high.

[0059] The solution containing bismuth basic nitrate and ferric sulfate contains acetic acid, and the acetic acid is used to acidify the mixture to increase its solubility.

[0060] After the hydrothermal reaction is completed, deionized water is used for filtering and washing, and all the precipitates in the mixed solution are filtered out. The filtrate is rinsed with deionized water, and after washing, it is dried to obtain bismuth ferrite powder.

[0061] It should be noted that the drying can be carried out by any device and at any temperature as long as the deionized water can be removed, such as oven drying at 70° C. for 4 hours.

[0062] The synthesis process of bismuth tungstate, bismuth vanadate and bismuth niobate is similar to that of bismuth ferrite, as follows.

[0063] Preparation method of bismuth tungstate:

[0064] According to the required molar mass fraction, the molar ratio of Bi to W is 2:1, and bismuth ions Bi are provided to 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) 3+ ) and sodium tungstate dihydrate (Na2WO4·2H2O, 0.1 mol / L, providing tungsten ions W 6+ ) solution until the bismuth ions and tungsten ions in the mixed solution are completely precipitated, filtered with deionized water, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used for stirring to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out. After the reaction is completed, the bismuth ferrite powder is obtained by filtering and drying.

[0065] The reaction temperature of the hydrothermal reaction is 200°C and the reaction time is 24h. The temperature and time will affect the purity of bismuth tungstate. At the above temperature and time, the purity of the obtained bismuth tungstate is high.

[0066] The solution containing basic bismuth nitrate and sodium tungstate dihydrate contains acetic acid, and the acetic acid is used to acidify the mixture to increase its solubility.

[0067] After the hydrothermal reaction is completed, deionized water is used for filtration and washing to filter out all the precipitates in the mixed solution, and the filtrate is rinsed with deionized water. After the washing is completed, it is dried to obtain bismuth tungstate powder.

[0068] It should be noted that the drying can be carried out by any device and at any temperature as long as the deionized water can be removed, such as oven drying at 70° C. for 4 hours.

[0069] Preparation method of bismuth vanadate powder:

[0070] According to the required molar mass fraction, the molar ratio of Bi to V is 2:1. 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) is added to provide bismuth ions Bi 3+ ) and ammonium metavanadate (NH4VO3, 0.1 mol / L, providing vanadium ions V 5+ ) solution until the bismuth ions and vanadium ions in the mixed solution are completely precipitated, filtered with deionized water, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used to stir the materials in the reactor to mix them evenly, and a hydrothermal reaction is carried out. After the reaction is completed, the bismuth vanadate powder is obtained by filtering and drying.

[0071] The reaction temperature of the hydrothermal reaction is 200°C and the reaction time is 24h. The temperature and time will affect the purity of bismuth vanadate. At the above temperature and time, the purity of the obtained bismuth vanadate is high.

[0072] The solution containing bismuth basic nitrate and ammonium metavanadate contains acetic acid, and the acetic acid is used to acidify the mixture to increase its solubility.

[0073] After the hydrothermal reaction is completed, deionized water is used for filtration and washing to filter out all the precipitates in the mixed solution, and the filtrate is rinsed with deionized water. After the washing is completed, it is dried to obtain bismuth vanadate powder.

[0074] It should be noted that the drying can be carried out by any device and at any temperature as long as the deionized water can be removed, such as oven drying at 70° C. for 4 hours.

[0075] Preparation method of bismuth niobate powder:

[0076] According to the required molar mass fraction, the molar ratio of Bi to Nb is 2:1, and bismuth ions Bi are provided to 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) 3+ ) and potassium hexaniobate (K 8-x H x Nb6O 19 nH2O, 0.1 mol / L, provides niobium ions Nb 5+) solution until the bismuth ions and niobium ions in the mixed solution are completely precipitated, filtered with deionized water, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used to stir to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out. After the reaction is completed, the bismuth niobate powder is obtained by filtering and drying.

[0077] The reaction temperature of the hydrothermal reaction is 200°C and the reaction time is 24 hours. The temperature and time will affect the purity of bismuth niobate. At the above temperature and time, the purity of the obtained bismuth niobate is high.

[0078] The solution containing bismuth basic nitrate and potassium hexaniobate contains acetic acid, and the acetic acid is used to acidify the mixture to increase its solubility.

[0079] After the hydrothermal reaction is completed, deionized water is used for filtering and washing, and all the precipitates in the mixed solution are filtered out. The filtrate is rinsed with deionized water, and after washing, it is dried to obtain bismuth niobate powder.

[0080] It should be noted that the drying can be carried out by any device and at any temperature as long as the deionized water can be removed, such as oven drying at 70° C. for 4 hours.

[0081] It should be noted that the bismuth ferrite / graphene oxide composite, bismuth tungstate / graphene oxide composite, bismuth vanadate / graphene oxide composite, bismuth niobate / graphene oxide composite, bismuth ferrite / carbon nanotube composite, bismuth tungstate / carbon nanotube composite, bismuth vanadate / carbon nanotube composite and / or bismuth niobate / carbon nanotube composite in the above-mentioned piezoelectric powder are conventional products, which can be purchased commercially or prepared by oneself.

[0082] The following method can be used to prepare bismuth ferrite / graphene oxide composites, bismuth tungstate / graphene oxide composites, bismuth vanadate / graphene oxide composites, bismuth niobate / graphene oxide composites, bismuth ferrite / carbon nanotube composites, bismuth tungstate / carbon nanotube composites, bismuth vanadate / carbon nanotube composites and / or bismuth niobate / carbon nanotube composites.

[0083] First, graphene oxide (GO) is prepared from natural graphite powder by a modified Hummers method. Preparation method of bismuth ferrite / graphene oxide composite:

[0084] According to the required molar mass fraction, the molar ratio of Bi to Fe is 1:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi3+ ) and ferrous sulfate (Fe2(SO4)3·7H2O, 0.1 mol / L, providing iron ions Fe 3+ ) solution; at the same time, take a certain amount of GO solution prepared in advance and add it to the above solution, ultrasonically vibrate for 3 hours and mechanically stir for 1 hour to obtain a suspension in which GO is evenly dispersed; add ammonia water to the suspension until the bismuth ions and iron ions in the suspension are completely precipitated, filter with deionized water, completely filter out the precipitate in the mixed solution, and rinse the filtrate with deionized water. Add a small amount of ammonia water (2M) and the filtrate to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, stir with a glass rod to mix the materials in the reactor evenly, and perform a hydrothermal reaction. The product is washed with deionized water and ethanol several times, dried, and finally a bismuth ferrite / graphene oxide (BiFeO3@GrO) composite material with a graphene oxide mass content of 1%, 3% and 5% is obtained.

[0085] Before the reaction, the reactor was cleaned with dilute nitric acid.

[0086] The solution containing bismuth basic nitrate and ferric sulfate contains acetic acid, and the acetic acid is used to acidify the mixture to increase the solubility.

[0087] The reaction temperature of the hydrothermal reaction is 200°C and the reaction time is 24h. The temperature and time will affect the purity of the bismuth ferrite / graphene oxide composite. At the above temperature and time, the purity of the obtained bismuth ferrite / graphene oxide composite is high.

[0088] After the hydrothermal reaction is completed, deionized water is used for filtration to filter out all the precipitates in the mixed solution, and the filtrate is rinsed with deionized water and ethanol. After washing, it is dried to obtain bismuth ferrite powder.

[0089] It should be noted that the drying can be carried out by any device and at any temperature as long as the deionized water and ethanol can be removed, such as oven drying at 70°C for 4 hours; or vacuum drying oven drying at 80°C for 24 hours.

[0090] The preparation method of bismuth ferrite / carbon nanotube composite is as follows: Figure 1 As shown (it should be noted that Figure 1 The synthesis reaction mechanism presented is applicable to all piezoelectric powders):

[0091] According to the required molar mass fraction, the molar ratio of Bi to Fe is 1:1, and 500mL 0.1mol / L bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1mol / L) is taken to provide bismuth ions Bi 3+) and ferrous sulfate (Fe2(SO4)3·7H2O, 0.1 mol / L, providing iron ions Fe 3+ ) solution; carbon nanotubes (CNTs) are purchased commercially, and different concentrations of 1%, 3% and 5% carbon nanotube alkaline solutions are prepared as needed; a certain amount of pre-prepared carbon nanotube alkaline solution is added to the above solution, ultrasonically vibrated for 3 hours and mechanically stirred for 1 hour to obtain a suspension in which CNTs are evenly dispersed; ammonia water is added to the suspension until the bismuth ions and iron ions in the suspension are completely precipitated, deionized water is used for filtering, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used for stirring to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out (after keeping warm at 200°C for 24 hours). The product was washed with deionized water and ethanol for several times and dried to finally obtain bismuth ferrite / carbon nanotube (BiFeO3@CNTs) composite materials with carbon nanotube mass contents of 1%, 3% and 5%.

[0092] Preparation method of bismuth tungstate / graphene oxide composite:

[0093] According to the required molar mass fraction, the molar ratio of Bi to W is 2:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and sodium tungstate dihydrate (Na2WO4·2H2O, 0.1 mol / L, providing tungsten ions W 6+ ) solution; at the same time, take a certain amount of GO solution prepared in advance and add it to the above solution, ultrasonically vibrate for 3 hours and mechanically stir for 1 hour to obtain a suspension in which GO is evenly dispersed; add ammonia water to the suspension until the bismuth ions and tungsten ions in the suspension are completely precipitated, filter with deionized water, completely filter out the precipitate in the mixed solution, and rinse the filtrate with deionized water. Add a small amount of ammonia water (2M) and the filtrate to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, stir with a glass rod to mix the materials in the reactor evenly, and perform a hydrothermal reaction (take out after keeping warm at 200°C for 24 hours). The product is washed with deionized water and ethanol several times, dried, and finally a bismuth tungstate / graphene oxide (Bi2WO6@GrO) composite material with a graphene oxide mass content of 1%, 3% and 5% is obtained.

[0094] Preparation method of bismuth tungstate / carbon nanotube composite:

[0095] According to the required molar mass fraction, the molar ratio of Bi to W is 2:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and sodium tungstate dihydrate (Na2WO4·2H2O, 0.1 mol / L, providing tungsten ions W 6+ ) solution; carbon nanotubes (CNTs) are purchased commercially, and different concentrations of 1%, 3% and 5% carbon nanotube alkaline solutions are prepared as needed; at the same time, a certain amount of pre-prepared carbon nanotube alkaline solution is added to the above solution, ultrasonically vibrated for 3 hours and mechanically stirred for 1 hour to obtain a suspension in which CNTs are evenly dispersed; ammonia water is added to the suspension until the bismuth ions and tungsten ions in the suspension are completely precipitated, deionized water is used for filtering, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used for stirring to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out (after keeping warm at 200°C for 24 hours). The product was washed with deionized water and ethanol for several times and dried to finally obtain bismuth tungstate / carbon nanotube (Bi2WO6@CNTs) composite materials with carbon nanotube mass contents of 1%, 3% and 5%.

[0096] Preparation method of bismuth vanadate / graphite oxide composite:

[0097] According to the required molar mass fraction, the molar ratio of Bi to V is 2:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and ammonium metavanadate (NH4VO3, 0.1 mol / L, providing vanadium ions V 5+ ) solution; at the same time, take a certain amount of GO solution prepared in advance and add it to the above solution, ultrasonically vibrate for 3 hours and mechanically stir for 1 hour to obtain a suspension in which GO is evenly dispersed; add ammonia water to the suspension until the bismuth ions and vanadium ions in the suspension are completely precipitated, filter with deionized water, completely filter out the precipitate in the mixed solution, and rinse the filtrate with deionized water. Add a small amount of ammonia water (2M) and the filtrate to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, stir with a glass rod to mix the materials in the reactor evenly, and perform a hydrothermal reaction (take out after keeping warm at 200°C for 24 hours). The product is washed several times with deionized water and ethanol, dried, and finally a bismuth vanadate / graphene oxide (BiVO4@GrO) composite material with a graphene oxide mass content of 1%, 3% and 5% is obtained.

[0098] Preparation method of bismuth vanadate / carbon nanotube composite:

[0099] According to the required molar mass fraction, the molar ratio of Bi to V is 2:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and ammonium metavanadate (NH4VO3, 0.1 mol / L, providing vanadium ions V 5+ ) solution; carbon nanotubes (CNTs) are purchased commercially, and different concentrations of 1%, 3% and 5% carbon nanotube alkaline solutions are prepared as needed; at the same time, a certain amount of pre-prepared carbon nanotube alkaline solution is added to the above solution, ultrasonically vibrated for 3 hours and mechanically stirred for 1 hour to obtain a suspension in which CNTs are evenly dispersed; ammonia water is added to the suspension until the bismuth ions and vanadium ions in the suspension are completely precipitated, deionized water is used for filtering, the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used for stirring to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out (taken out after keeping warm at 200°C for 24 hours). The product was washed several times with deionized water and ethanol, and dried, and finally a bismuth vanadate / carbon nanotube (BiVO4@CNTs) composite material with a carbon nanotube mass content of 1%, 3% and 5% was obtained.

[0100] Preparation method of bismuth niobate / graphene oxide composite:

[0101] According to the required molar mass fraction, the molar ratio of Bi to Nb is 2:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and potassium hexaniobate (K 8-x H x Nb6O 19 nH2O, 0.1 mol / L, provides niobium ions Nb 5+) solution; at the same time, take a certain amount of GO solution prepared in advance and add it to the above solution, ultrasonically vibrate for 3 hours and mechanically stir for 1 hour to obtain a suspension in which GO is evenly dispersed; add ammonia water to the suspension until the bismuth ions and niobium ions in the suspension are completely precipitated, filter with deionized water, completely filter out the precipitate in the mixed solution, and rinse the filtrate with deionized water. Add a small amount of ammonia water (2M) and the filtrate to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, stir with a glass rod to mix the materials in the reactor evenly, and perform a hydrothermal reaction (take out after keeping warm at 200℃ for 24 hours). The product is washed with deionized water and ethanol several times, dried, and finally obtains bismuth niobate / graphene oxide (Bi3NbO7@GrO) composite materials with a graphene oxide mass content of 1%, 3% and 5%.

[0102] Preparation method of bismuth niobate / carbon nanotube composite:

[0103] According to the required molar mass fraction, the molar ratio of Bi to Nb is 2:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and potassium hexaniobate (K 8-x H x Nb6O 19 nH2O, 0.1 mol / L, provides niobium ions Nb 5+ ) solution; carbon nanotubes (CNTs) are purchased commercially, and different concentrations of 1%, 3% and 5% carbon nanotube alkaline solutions are prepared as needed; at the same time, a certain amount of pre-prepared carbon nanotube alkaline solution is added to the above solution, ultrasonically vibrated for 3 hours and mechanically stirred for 1 hour to obtain a suspension in which the carbon nanotube alkaline solution is evenly dispersed; ammonia water is added to the suspension until the bismuth ions and niobium ions in the suspension are completely precipitated, and deionized water is used for filtration, and the precipitate in the mixed solution is completely filtered out, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to a 150mL Teflon thermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used for stirring to mix the materials in the reactor evenly, and a hydrothermal reaction is carried out (after keeping warm at 200°C for 24 hours). The product was washed with deionized water and ethanol for several times and dried to finally obtain bismuth niobate / carbon nanotube (Bi3NbO7@CNTs) composite materials with carbon nanotube mass contents of 1%, 3% and 5%.

[0104] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the piezoelectric powder is a micro-nano powder.

[0105] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the piezoelectric high molecular polymer is a thermoplastic. Thermoplastics can be softened or melted repeatedly, which is convenient for mold processing. The use of thermoplastic materials can improve the operability and service life of the intelligent piezoelectric responsive polymer-based self-lubricating material, and adding a certain amount of piezoelectric powder to the thermoplastic can enhance its piezoelectric properties, and can ensure that the intelligent piezoelectric responsive polymer-based self-lubricating material has good mechanical properties (wear resistance, etc.) and has excellent piezoelectric properties.

[0106] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the piezoelectric high molecular polymer includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11, perfluoroethylene propylene copolymer, modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 and / or modified perfluoroethylene propylene copolymer. The above-mentioned piezoelectric high molecular polymers all have excellent piezoelectricity, wear resistance, lubrication, mechanical strength, and also have excellent resistance to ultraviolet rays and high-energy radiation.

[0107] It should be noted that the polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11, and perfluoroethylene-propylene copolymer are conventional products and can be purchased commercially. The modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11, and / or modified perfluoroethylene-propylene copolymer are obtained by modification with ionic liquids, and the modification method is the same.

[0108] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the modification is to use an alkyl imidazole ionic liquid with conductivity as a modifier, and obtain modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 or modified perfluoroethylene propylene copolymer by melt blending.

[0109] In the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention, the alkyl imidazole ionic liquid is one of 1-butyl-3-methylimidazole bromide, 1-butyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole tetrafluoroborate, 1-butyl-3-methylimidazole hexafluorophosphate and 1-butyl-3-methylimidazole hydrogen sulfate.

[0110] The structures of the five ionic liquids are as follows:

[0111]

[0112]

[0113] It should be noted that the preparation method of the modified polymer is as follows: Figure 2 As shown (it should be noted that Figure 2 The modified composite material is obtained by melt blending polyvinylidene fluoride and polyvinyl chloride as polymer matrix and 1-butyl-3-methylimidazole bromide as modifier. The modified composite material and piezoelectric powder bismuth ferrite are ground and mixed to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material):

[0114] Polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11 or perfluoroethylene-propylene copolymer with high intrinsic dielectric constant, low dielectric loss and good mechanical properties were selected as the polymer matrix, and five conductive alkyl imidazolium ionic liquids (ILs): 1-butyl-3-methylimidazolium bromide ([Bmim]Br), 1-butyl-3-methylimidazolium chloride ([Bmim]Cl), 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]Br), and 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]Cl) were used as the ionic liquids. m]BF4), 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6) or 1-butyl-3-methylimidazolium hydrogen sulfate ([Bmim]HSO4) as modifiers, and ionic liquid IL modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11, and modified perfluoroethylene propylene copolymer composites are prepared by melt blending, and the microstructure, electrical properties, etc. of the composites are tested.

[0115] Before melt blending, the polymer matrix needs to be dried to remove moisture therein. Preferably, the polymer matrix can be placed in a vacuum oven at 70° C. for 24 hours to remove moisture from the sample.

[0116] Among them, a rheometer can be used for melt blending, each blending system weighs 50g, the ionic liquid percentage can be 2-10wt%, specifically 2wt%, 4wt%, 6wt%, 8wt% or 10wt%, etc., the blending temperature is 200°C, the rotor speed is 120r / min, and the blending time is 10min. After blending, an ionic liquid IL modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 or modified perfluoroethylene-propylene copolymer composite material is obtained.

[0117] Taking polyvinylidene fluoride as an example, 1-butyl-3-methylimidazole bromide is used as a modifier, and a rheometer is used for melt blending. The blending system weighs 50g, the percentage of 1-butyl-3-methylimidazole bromide is 8wt%, the blending temperature is 200℃, the rotor speed is 120r / min, and the blending time is 10min. After blending, modified polyvinylidene fluoride is obtained. After testing, the conductivity of the modified polyvinylidene fluoride is 2.5×10 -14 Sm -1, which is 10 orders of magnitude higher than the conductivity of pure polyvinylidene fluoride. The dielectric constant of pure polyvinylidene fluoride is about 8.1 at 1000Hz, while the dielectric constant of modified polyvinylidene fluoride is increased to 65 at the same frequency, which is about 8 times that of pure polyvinylidene fluoride. It can be seen that this modification can greatly improve the piezoelectric properties of the polymer matrix itself.

[0118] In the intelligent piezoelectric response polymer-based self-lubricating material provided by the present invention, the piezoelectric polymer is preferably ionic liquid modified vinylidene fluoride (IL-PVDF). IL-PVDF is a semi-crystalline polymer under normal conditions. IL-PVDF applications are mainly concentrated in the three major fields of petrochemicals, electronics and coatings. IL-PVDF has good piezoelectricity, chemical resistance, processability, fatigue resistance and creep resistance. IL-PVDF is known for its excellent chemical stability, piezoelectricity and electrical insulation. In the semiconductor industry, it is widely used for storing and transporting high-purity chemicals. The application of IL-PVDF resin in the field of lithium-ion batteries is rapidly driving the growth of its demand and has become one of the fastest growing areas on the market. As the main raw material of fluorocarbon coatings, coatings made of IL-PVDF resins have been developed to the sixth generation. Because of its excellent weather resistance, it can be used outdoors for a long time without maintenance and is widely used in power facilities, aviation facilities, transportation infrastructure and high-rise buildings. In addition, IL-PVDF resin can also be mixed with other resins to improve performance. For example, composite materials made by mixing with ABS resin have been widely used in construction, automotive interiors, and home appliance housings.

[0119] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention comprises, by volume percentage: 1-10% piezoelectric powder and 90-99% piezoelectric high molecular polymer.

[0120] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention comprises, by volume percentage: 1-10% piezoelectric powder and 90-99% piezoelectric high molecular polymer;

[0121] The piezoelectric powder is one of bismuth ferrite, bismuth tungstate, bismuth vanadate or bismuth niobate.

[0122] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention comprises, by volume percentage: 5% piezoelectric powder and 95% piezoelectric high molecular polymer;

[0123] The piezoelectric powder is bismuth ferrite, and the piezoelectric high molecular polymer is polyvinylidene fluoride.

[0124] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention comprises, by volume percentage: 3-7% piezoelectric powder and 93-97% piezoelectric high molecular polymer;

[0125] The piezoelectric powder is one of bismuth ferrite, bismuth tungstate, bismuth vanadate or bismuth niobate;

[0126] The piezoelectric high molecular polymer is a material modified by melt blending with alkyl imidazole ionic liquid as a modifier and polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11 or perfluoroethylene-propylene copolymer as a polymer matrix.

[0127] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention comprises, by volume percentage: 5% piezoelectric powder and 95% piezoelectric high molecular polymer;

[0128] The piezoelectric powder is bismuth ferrite, and the piezoelectric high molecular polymer is polyvinylidene fluoride modified by alkyl imidazole ionic liquid.

[0129] The intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention comprises, by volume percentage: 5% piezoelectric powder and 95% piezoelectric high molecular polymer;

[0130] The piezoelectric powder is a bismuth ferrite / graphene oxide composite and a bismuth ferrite / carbon nanotube composite, and the piezoelectric polymer is polyvinylidene fluoride modified by an alkyl imidazole ionic liquid. Experiments have shown that the intelligent piezoelectric responsive polymer-based self-lubricating material with piezoelectric IL-PVDF as the matrix and BiFeO3@CNTs or BiFeO3@GrO as the piezoelectric powder filler has excellent wear resistance, piezoelectricity, self-lubricating properties, and has a high homogeneous charge characteristic.

[0131] Figure 3 The charge repulsion mechanism diagram of the intelligent piezoelectric response polymer-based self-lubricating material provided by the present invention is a diagram with bismuth ferrite / carbon nanotube composite as piezoelectric powder and polyvinylidene fluoride as polymer matrix. It can be seen from the figure that the intelligent piezoelectric response polymer-based self-lubricating material composed of bismuth ferrite / carbon nanotube composite (BiFeO2@CNTs) and polyvinylidene fluoride (PVDF) rubs against GCr15 steel. The shear force generated by friction causes the surface of the intelligent self-lubricating material and the steel material to be mutually damaged. As the load increases, the surface wear becomes more serious, and the material transfer of the two will also be more. In addition, due to the increase in friction temperature, some plastic molecular chains will also be broken, which will lead to the occurrence of melting and plasticization, and the molecular chain rupture will also produce a large number of free radicals, which will promote the transfer of charge. Due to the charge repulsion, the same charges repel each other, reduce friction, reduce wear, and form an intelligent self-lubricating effect.

[0132] Figure 4The charge repulsion mechanism diagram of the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention is shown in the figure, which uses bismuth ferrite / carbon nanotube composite as piezoelectric powder and polyvinylidene fluoride as polymer matrix. It can be seen from the figure that the intelligent piezoelectric responsive polymer-based self-lubricating material is negatively triboelectric, while the matrix (taking bearing steel as an example) is positively triboelectric. When the two are not in contact, there is no charge on the surface. When an external force is applied directly above the generator, the bearing steel matrix moves downward and contacts the intelligent self-lubricating material, and the electrons on the surface of the bearing steel matrix are transferred to the surface of the intelligent self-lubricating material and make the surface of the intelligent self-lubricating material negatively charged, while the same amount of positive charges are distributed on the surface of the relative bearing steel matrix. When the bearing steel matrix and the intelligent self-lubricating material are separated from each other, the bottom bearing steel matrix generates positive charges due to electrostatic induction, and the electrons migrate from the bottom bearing steel matrix to the top bearing steel matrix through the external circuit. When the intelligent self-lubricating material is completely separated from the bearing steel matrix, the charges between the two bearing steel matrixes are balanced, and there is no potential difference at this time, and there is no electron migration, and the above process is repeated thereafter. In the above process, due to the material transfer at the material transfer point, an extremely thin transfer film is formed on the friction surface, which fills the gap between the contact surfaces, reduces the friction coefficient, and achieves an intelligent self-lubricating effect.

[0133] A second typical embodiment of the present invention provides a method for preparing the above-mentioned intelligent piezoelectric responsive polymer-based self-lubricating material, comprising:

[0134] The piezoelectric powder and the piezoelectric high molecular polymer are mixed in proportion to obtain a mixed material, and the mixed material is molded to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

[0135] In the preparation method provided by the present invention, the molding is compression molding or injection molding;

[0136] The compression molding has a molding pressure of 6-24 MPa and a molding temperature of 350-390°C.

[0137] The compression molding specifically includes the following steps: placing the mixture into a vulcanizer for sintering, and then pressurizing and cooling the mixture obtained after sintering, and obtaining the intelligent piezoelectric responsive polymer-based self-lubricating material after cooling to room temperature.

[0138] Among them, the pressure used in compression molding is 6 to 24 MPa. Experiments show that the pressure will affect the finished product effect of the intelligent piezoelectric responsive polymer-based self-lubricating material. If the pressure is too small, it will cause too many bubbles to form inside the pressed intelligent piezoelectric responsive polymer-based self-lubricating material, and will also affect the piezoelectric and mechanical properties of the intelligent piezoelectric responsive polymer-based self-lubricating material. On the contrary, excessive pressure will fracture the intelligent piezoelectric responsive polymer-based self-lubricating material, thus affecting its use.

[0139] The temperature used for compression molding is 350-390°C. Experiments have shown that the temperature will affect the finished product effect of the intelligent piezoelectric responsive polymer-based self-lubricating material. If the temperature is too high, the intelligent piezoelectric responsive polymer-based self-lubricating material will crack during the pressing process, making it unusable. If the temperature is too low, the internal part of the intelligent piezoelectric responsive polymer-based self-lubricating material will not be able to be formed during the pressing process.

[0140] A third typical embodiment of the present invention provides an application of the above-mentioned intelligent piezoelectric responsive polymer-based self-lubricating material or the intelligent piezoelectric responsive polymer-based self-lubricating material prepared by the above-mentioned preparation method in a robot.

[0141] In the application provided by the present invention, the intelligent piezoelectric responsive polymer-based self-lubricating material is used in the movable joints of the robot.

[0142] It should be noted that the intelligent piezoelectric responsive polymer-based self-lubricating material obtained after compression molding can be used directly, or can be processed into a desired shape as needed before use. Preferably, the processing includes processing using an angle grinder, a grinding wheel or other devices.

[0143] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0144] Example 1

[0145] An intelligent piezoelectric responsive polymer-based self-lubricating material, comprising, by volume percentage: 5% bismuth ferrite nanopowder and 95% polyvinylidene fluoride, and the preparation method thereof is as follows:

[0146] According to the required molar mass fraction, the molar ratio of Bi to Fe is 1:1, and bismuth ions Bi are provided to 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) 3+ ) and ferrous sulfate (Fe2(SO4)3·7H2O, 0.1 mol / L, providing iron ions Fe 3+ ) solution until the bismuth ions and iron ions in the mixed solution are completely precipitated, and the mixture is filtered with deionized water to completely filter out the precipitate in the mixed solution, and the filtrate is rinsed with deionized water. A small amount of ammonia water (2M) and the filtrate are added to a 150mL hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, and a glass rod is used to stir the materials in the reactor to mix them evenly, and a hydrothermal reaction is carried out (200°C, 24h). After the reaction is completed, filter, and dry at 70°C for 4h to obtain bismuth ferrite powder. The synthesized bismuth ferrite was scanned by scanning electron microscopy. As Figure 5As shown, bismuth ferrite presents flake aggregation, and the aggregation effect is produced because bismuth ferrite has ferroelectricity and ferromagnetism.

[0147] Bismuth ferrite nanopowder and polyvinylidene fluoride are mixed in proportion to obtain a mixture, which is molded at a molding pressure of 15 MPa and a molding temperature of 370° C. to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

[0148] Example 2

[0149] An intelligent piezoelectric responsive polymer-based self-lubricating material, comprising, by volume percentage: 5% bismuth ferrite nanopowder, 95% ionic liquid modified polyvinylidene fluoride, and the preparation method thereof is as follows:

[0150] With polyvinylidene fluoride as the polymer matrix and 1-butyl-3-methylimidazole bromide as the modifier, a rheometer was used for melt blending. The blending system weighed 50g, the percentage of 1-butyl-3-methylimidazole bromide was 8wt%, the blending temperature was 200°C, the rotor speed was 120r / min, and the blending time was 10min. After blending, ionic liquid modified polyvinylidene fluoride was obtained. After testing, the conductivity of the modified polyvinylidene fluoride was 2.5×10 -14 Sm -1 , which is 10 orders of magnitude higher than the conductivity of pure polyvinylidene fluoride. The dielectric constant of pure polyvinylidene fluoride is about 8.1 at 1000Hz, while the dielectric constant of modified polyvinylidene fluoride is increased to 65 at the same frequency, which is about 8 times that of pure polyvinylidene fluoride.

[0151] Bismuth ferrite nanopowder and ionic liquid modified polyvinylidene fluoride are mixed in proportion to obtain a mixture, which is compression molded at a molding pressure of 15 MPa and a molding temperature of 370° C. to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

[0152] Example 3

[0153] An intelligent piezoelectric responsive polymer-based self-lubricating material, comprising, by volume percentage: 5% bismuth ferrite / graphene oxide composite nanopowder, 95% ionic liquid modified polyvinylidene fluoride, and the preparation method thereof is as follows:

[0154] With polyvinylidene fluoride as a polymer matrix and 1-butyl-3-methylimidazole bromide as a modifier, a rheometer is used for melt blending, the blending system weighs 50g, the content of 1-butyl-3-methylimidazole bromide is 8wt%, the blending temperature is 200°C, the rotor speed is 120r / min, the blending time is 10min, and after blending, ionic liquid modified polyvinylidene fluoride is obtained.

[0155] According to the required molar mass fraction, the molar ratio of Bi to Fe is 1:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and ferrous sulfate (Fe2(SO4)3·7H2O, 0.1 mol / L, providing iron ions Fe 3+ ) solution; at the same time, take a certain amount of GO solution prepared in advance and add it to the above solution, ultrasonically vibrate for 3 hours and mechanically stir for 1 hour to obtain a suspension in which GO is evenly dispersed; add ammonia water to the suspension until the bismuth ions and iron ions in the suspension are completely precipitated, filter with deionized water, completely filter out the precipitate in the mixed solution, and rinse the filtrate with deionized water. Add a small amount of ammonia water (2M) and the filtrate to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, use a glass rod to stir to mix the materials in the reactor evenly, and perform a hydrothermal reaction. The product is washed with deionized water and ethanol several times, placed in a vacuum drying oven at 80°C for 24 hours, and finally a bismuth ferrite / graphene oxide (BiFeO3@GrO) composite material with a graphene oxide mass content of 5% is obtained.

[0156] The bismuth ferrite / graphene oxide composite nanopowder and the ionic liquid modified polyvinylidene fluoride are mixed in proportion to obtain a mixture, which is compression molded at a molding pressure of 15 MPa and a molding temperature of 370° C. to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

[0157] Example 4

[0158] An intelligent piezoelectric responsive polymer-based self-lubricating material, comprising, by volume percentage: 5% bismuth ferrite / carbon nanotube composite nanopowder, 95% ionic liquid modified polyvinylidene fluoride, and the preparation method thereof is as follows:

[0159] With polyvinylidene fluoride as a polymer matrix and 1-butyl-3-methylimidazole bromide as a modifier, a rheometer is used for melt blending, the blending system weighs 50g, the content of 1-butyl-3-methylimidazole bromide is 8wt%, the blending temperature is 200°C, the rotor speed is 120r / min, the blending time is 10min, and after blending, ionic liquid modified polyvinylidene fluoride is obtained.

[0160] According to the required molar mass fraction, the molar ratio of Bi to Fe is 1:1. Take 500 mL of bismuth basic nitrate ([Bi6O6(OH)3](NO3)3·1.5H2O, 0.1 mol / L) to provide bismuth ions Bi 3+ ) and ferrous sulfate (Fe2(SO4)3·7H2O, 0.1 mol / L, providing iron ions Fe 3+) solution; at the same time, take a certain amount of pre-prepared alkaline carbon nanotube solution and add it to the above solution, ultrasonically vibrate for 3 hours and mechanically stir for 1 hour to obtain a suspension in which CNTs are evenly dispersed; add ammonia water to the suspension until the bismuth ions and iron ions in the suspension are completely precipitated, filter with deionized water, completely filter out the precipitate in the mixed solution, and rinse the filtrate with deionized water. Add a small amount of ammonia water (2M) and the filtrate to the hydrothermal reactor, ensuring that the total volume of each material added to the reactor does not exceed 1 / 3 of the total volume of the lining of the hydrothermal reactor, use a glass rod to stir to mix the materials in the reactor evenly, and perform a hydrothermal reaction. The product is washed with deionized water and ethanol several times, placed in a vacuum drying oven at 80°C for 24 hours, and finally a bismuth ferrite / carbon nanotube (BiFeO3@CNTs) composite material with a carbon nanotube mass content of 5% is obtained.

[0161] The bismuth ferrite / graphene oxide composite nanopowder and the ionic liquid modified polyvinylidene fluoride are mixed in proportion to obtain a mixture, which is compression molded at a molding pressure of 15 MPa and a molding temperature of 370° C. to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

[0162] Example 5

[0163] An intelligent piezoelectric responsive polymer-based self-lubricating material comprises, by volume percentage, 5% bismuth tungstate nanopowder and 95% polyvinylidene fluoride. The preparation method thereof is different from that of Example 1 in that ferric sulfate is replaced by sodium tungstate dihydrate, and the remaining steps are consistent with those of Example 1.

[0164] Example 6

[0165] An intelligent piezoelectric responsive polymer-based self-lubricating material comprises, by volume percentage, 5% bismuth vanadate nanopowder and 95% polyvinylidene fluoride. The preparation method thereof is different from that of Example 1 in that ferric sulfate is replaced by ammonium metavanadate, and the remaining steps are consistent with those of Example 1.

[0166] Example 7

[0167] An intelligent piezoelectric responsive polymer-based self-lubricating material comprises, by volume percentage, 5% bismuth niobate nanopowder and 95% polyvinylidene fluoride. The preparation method thereof is different from that of Example 1 in that ferric sulfate is replaced by potassium hexaniobate, and the remaining steps are consistent with those of Example 1.

[0168] Performance Verification

[0169] The intelligent piezoelectric responsive polymer-based self-lubricating material obtained in the embodiment was cut according to the test requirements, and a pin-on-disc test was carried out using a Pin-On-Disc (POD) tribometer (Wazau, Germany). The material was run at a speed of 0.05 m / s for 3 h under pressures of 5 N, 10 N, and 20 N, respectively, to detect changes in friction coefficient and wear.

[0170] from Figure 6 , Figure 7 It can be seen that with the increase of load, the friction coefficient and friction loss of the intelligent piezoelectric responsive polymer-based self-lubricating material provided in Example 1 of the present invention are lower than those of pure PVDF, and the changes in the friction coefficient and friction loss between the blended materials show a trend of first decreasing and then increasing, which indicates that the intelligent piezoelectric responsive polymer-based self-lubricating material provided by the present invention has the effect of reducing the friction coefficient, reducing friction loss, and extending the service life of the robot joints.

[0171] The performance of the intelligent piezoelectric responsive polymer-based self-lubricating materials provided in Examples 2-4 of the present invention is similar to that of Example 1. As the load increases, the friction coefficient of the material first decreases and then increases, and the friction loss also first decreases and then increases. Under a pressure of 10N, the minimum friction coefficient is arranged from small to large, and it is Example 3 = Example 4 < Example 2 < Example 1; the minimum friction loss is arranged from small to large, and it is Example 3 = Example 4 < Example 2 < Example 1. It can be seen that the intelligent piezoelectric responsive polymer-based self-lubricating material with piezoelectric IL-PVDF as the matrix and BiFeO3@CNTs or BiFeO3@GrO as the piezoelectric powder filler has excellent wear resistance, piezoelectricity, self-lubricating properties, and has a high homogeneous charge characteristic.

[0172] The performance of the intelligent piezoelectric responsive polymer-based self-lubricating materials provided in Examples 5-7 of the present invention is similar to that of Example 1. The friction coefficient of the material first decreases and then increases, and the friction loss also first decreases and then increases. Figure 8 As shown, the minimum friction coefficient is arranged from small to large, that is, Example 5 < Example 7 < Example 6; Fig. 9 The lowest friction loss is arranged from small to large as Example 5 < Example 7 < Example 6.

[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An intelligent piezoelectric responsive polymer-based self-lubricating material, characterized in that: Calculated by volume percentage, it includes: 1-15% piezoelectric powder, 85-99% piezoelectric high molecular polymer; The piezoelectric powder is an oxide containing bismuth and other metals, or a composite of the oxide and a carbon material.

2. The smart piezoelectric responsive polymer-based self-lubricating material according to claim 1, characterized in that: The piezoelectric powder is selected from at least one of bismuth ferrite, bismuth tungstate, bismuth vanadate, bismuth niobate, bismuth ferrite / graphene oxide composite, bismuth tungstate / graphene oxide composite, bismuth vanadate / graphene oxide composite, bismuth niobate / graphene oxide composite, bismuth ferrite / carbon nanotube composite, bismuth tungstate / carbon nanotube composite, bismuth vanadate / carbon nanotube composite and / or bismuth niobate / carbon nanotube composite; Preferably, the piezoelectric powder is micro-nano powder.

3. The smart piezoelectric responsive polymer-based self-lubricating material according to claim 1, characterized in that: The piezoelectric high molecular polymer includes one or more of polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11, perfluoroethylene-propylene copolymer, modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 and / or modified perfluoroethylene-propylene copolymer; Preferably, the modification is to use an alkyl imidazole ionic liquid with conductivity as a modifier, and obtain modified polyvinylidene fluoride, modified polyacrylonitrile, modified polyamide-imide, modified polyvinyl chloride, modified nylon 11 or modified perfluoroethylene-propylene copolymer by melt blending; Further preferably, the alkyl imidazole ionic liquid is one of 1-butyl-3-methyl imidazole bromide, 1-butyl-3-methyl imidazole chloride, 1-butyl-3-methyl imidazole tetrafluoroborate, 1-butyl-3-methyl imidazole hexafluorophosphate and 1-butyl-3-methyl imidazole hydrogen sulfate.

4. The intelligent piezoelectric responsive polymer-based self-lubricating material according to any one of claims 1 to 3, characterized in that: Calculated by volume percentage, it comprises: 1-10% piezoelectric powder and 90-99% piezoelectric high molecular polymer.

5. The intelligent piezoelectric responsive polymer-based self-lubricating material according to any one of claims 1 to 3, characterized in that: By volume percentage, it includes: 1-10% piezoelectric powder, 90-99% piezoelectric high molecular polymer; The piezoelectric powder is one of bismuth ferrite, bismuth tungstate, bismuth vanadate or bismuth niobate; Preferably, by volume percentage, it comprises: 5% piezoelectric powder, 95% piezoelectric high molecular polymer; The piezoelectric powder is bismuth ferrite, and the piezoelectric high molecular polymer is polyvinylidene fluoride.

6. The intelligent piezoelectric responsive polymer-based self-lubricating material according to any one of claims 1 to 3, characterized in that: By volume percentage, it includes: 3-7% piezoelectric powder, 93-97% piezoelectric high molecular polymer; The piezoelectric powder is one of bismuth ferrite, bismuth tungstate, bismuth vanadate or bismuth niobate; The piezoelectric high molecular polymer is a material modified by melt blending with an alkyl imidazole ionic liquid as a modifier and polyvinylidene fluoride, polyacrylonitrile, polyamide-imide, polyvinyl chloride, nylon 11 or perfluoroethylene-propylene copolymer as a polymer matrix; Preferably, by volume percentage, it comprises: 5% piezoelectric powder, 95% piezoelectric high molecular polymer; The piezoelectric powder is bismuth ferrite, and the piezoelectric high molecular polymer is polyvinylidene fluoride modified by alkyl imidazole ionic liquid.

7. A method for preparing the intelligent piezoelectric responsive polymer-based self-lubricating material according to any one of claims 1 to 6, characterized in that: include: The piezoelectric powder and the piezoelectric high molecular polymer are mixed in proportion to obtain a mixed material, and the mixed material is molded to obtain an intelligent piezoelectric responsive polymer-based self-lubricating material.

8. The preparation method according to claim 7, characterized in that: The molding is compression molding or injection molding; The compression molding has a molding pressure of 6-24 MPa and a molding temperature of 350-390°C.

9. Use of the intelligent piezoelectric responsive polymer-based self-lubricating material according to any one of claims 1 to 6 or the intelligent piezoelectric responsive polymer-based self-lubricating material prepared by the preparation method according to claim 7 or 8 in a robot.

10. The use according to claim 9, characterized in that Smart piezoelectric responsive polymer-based self-lubricating materials are used in the movable joints of robots.

Citation Information

Patent Citations

  • Lightweight wear-resistant polytetrafluoroethylene self-lubricating composite material and preparation method thereof

    CN116925483A

  • Fluorine-containing polymer mixing material and method for preparing bulb buffer ball keyway by same

    CN102952360A

  • Method for preparing bismuth tungstate / polyvinylidene fluoride composite material

    CN104877277A

  • Piezoresistive / piezoelectric interlayer material and preparation and application methods thereof, and interlayer type sensor and preparation and application methods thereof

    CN105953821A

  • Macromolecule piezoelectric composite material as well as preparation method and application thereof

    CN106751250A